Consolidation of territorial communities as a social project (Revista de Investigaciones Universidad del Quindío, 2022)
This article’s primary aim is a conceptual substantiation of the necessary conditions, and objective and subjective limitations of the social design for the consolidation route of territorial communities, which is understood as the process of mass consciousness modifications through the gradual prerequisites approval that ensure the assimilation of consolidation notions as behavioral standards. To gratify the study’s aim, a survey was conducted in the Belgorod region from Jan. to Apr. 2021, including a mass questionnaire survey of the people utilizing the quota sampling method. Based on the results, the system of social practice may be created in the territorial community; it can be inclined toward its participation in and reproduction as a dynamic participant in social processes.
Keywords: social consolidation; social solidarity; territorial community; social design